2008
DOI: 10.1017/s1041610208007874
|View full text |Cite
|
Sign up to set email alerts
|

Narratives in a users' and carers' group: meanings and impact

Abstract: The narratives provided a means of sharing carers' experiences and creating initiatives for further action by the Group. They have an impact on the people who hear or read them but may also be therapeutic for those who produce them. Narratives can also be a powerful tool in teaching and training, and in identifying areas for service and professional improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
(16 reference statements)
1
12
0
Order By: Relevance
“…The observed improvement in depression scores for our PD patients after the narrative program was anticipated and is consistent with the reported long-term improvement in emotional and physical health after expressive writing observed in a variety of illnesses [3] [5]. On the other hand, the worsening of depression among the caregivers was unexpected and may have been related to being encouraged to recognize and express feelings that may have been previously suppressed or seeing the decline of more advanced patients in the group which may have forced them out of denial or have threatened their feelings of optimism or hope.…”
Section: Discussionsupporting
confidence: 87%
“…The observed improvement in depression scores for our PD patients after the narrative program was anticipated and is consistent with the reported long-term improvement in emotional and physical health after expressive writing observed in a variety of illnesses [3] [5]. On the other hand, the worsening of depression among the caregivers was unexpected and may have been related to being encouraged to recognize and express feelings that may have been previously suppressed or seeing the decline of more advanced patients in the group which may have forced them out of denial or have threatened their feelings of optimism or hope.…”
Section: Discussionsupporting
confidence: 87%
“…As many studies did not provide detailed demographic information, it was unclear whether level of education or socioeconomic status impacted on awareness of dementia and help-seeking behaviour. Studies suggest that in some cases doctors are slow to recognise symptoms or reluctant to give a diagnosis [38],[39],[68],[74],[88],[92],[124], and that even when people have been referred to memory services the process may be slow, with long periods of waiting [93],[152].…”
Section: Resultsmentioning
confidence: 99%
“…Spouses had to adjust to increasingly unequal relationships [30],[54],[63],[64],[97],[104],[114],[123],[125], and communication between the couple was often affected. However, studies looking at the experiences of couples often found an emphasis on working together as a team, with a high degree of mutuality [39],[50],[88],[91],[110],[134]. It was clear that there was often significant strain on carers [39],[42],[44],[56],[109],[119],[123],[127], which often impacted adversely on their own health [43],[44],[61],[78],[117].…”
Section: Resultsmentioning
confidence: 99%
“…As reported by others (Hinton et al ., ; Hutchings et al ., ; Leung et al ., ; Robinson et al ., ; Chrisp et al ., ), participants' accounts in this study suggest that memory problems are the predominant reason for seeking help, and most approached their GP initially. Encounters with GPs were generally positive, contrary to previous criticisms of the attitudes of primary care physicians towards people presenting with self‐reported memory problems or symptoms of cognitive impairment (Bamford et al ., ; Downs et al ., ; Benbow et al ., ). Assessment in secondary care was reported less favourably, with participants feeling lost amongst the labyrinth of tests, score sheets, scans and appointments, with little knowledge over what constituted a ‘good’ (self) memory performance amongst the battery of neuropsychological tests.…”
Section: Discussionmentioning
confidence: 98%